Gwyn Steinbeck with Nathaniel Benchley - unknown:::Creator::::::::::::
Gwyn Steinbeck and humorist Nathaniel Benchley. Four photo-machine poses. See also numbers 0-020 and 0-060.Original is in the safe (in strip).